Effect of smartphone application with reminder on total fluid intake adequacy and hydration status among adults in Bontang, East Kalimantan - Handayani Eka Puspita Sari; Diana Sunardi; Krisadelfa Sutanto; Dian Novita Chandra; Dewi Friska; Putri Novia Choiri Insani (World Nutrition Journal, 2024)
Background: About 41% adults in Kalimantan have inadequate total fluid intake (TFI), which is higher than national inadequacy (28%). Inadequate TFI may cause dehydration. The biggest barrier to comply with TFI is to forget to drink. Smartphone application, Hidrasiku with reminder, is expected to be useful in TFI adequacy which may affect hydration status. Objective: This study aims to determine the effect of the Hidrasiku with reminder on the TFI adequacy and hydration status among adults in Bontang. Methods: The design of this study was quasi-experimental and cluster sampling. Inclusion criteria were healthy men, age 19-64 years and having a smartphone. Participants suffering with diseases that affected fluid balance and on diet and fluid restriction were excluded. Data collection was conducted from April to June 2023 in Bontang. A total of 106 participants were allocated into two groups, intervention and control. Both groups used Hidrasiku for four weeks, with the intervention group activating the reminder while the control group didn’t. Adequacy of TFI and hydration status were assessed before-after intervention. Results: A sample of 87 participants completed the study. The median age of the participants was 32 (19-61) years. At the end of intervention, there was significant difference in the TFI adequacy (90.2% vs 63.0%; p=0.003) and a significant increase in TFI +240 mL/day vs – 62.8 mL/day; p=0.002). Meanwhile no significant difference on hydration status (87.8% vs 73.9%; p=0.103). Conclusions: Hidrasiku with reminder has effect on the TFI adequacy and no effect on hydration status